Role of YHM1, encoding a mitochondrial carrier protein, in iron distribution of yeast. - Lesuisse, Emmanuel (2004)
Mitochondrial carrier proteins are a large protein family, consisting of 35 members in Saccharomyces cerevisiae. Members of this protein family have been shown to transport varied substrates from cytoplasm to mitochondria or mitochondria to cytoplasm, although many family members do not have assigned substrates. We speculated whether one or more of these transporters will play a role in iron metabolism. Haploid yeast strains each deleted for a single mitochondrial carrier protein were analysed for alterations in iron homoeostasis. The strain deleted for YHM1 was characterized by increased and misregulated surface ferric reductase and high-affinity ferrous transport activities. Siderophore uptake from different sources was also increased, and these effects were dependent on the AFT1 iron sensor regulator. Mutants of YHM1 converted into rho degrees, consistent with secondary mitochondrial DNA damage from mitochondrial iron accumulation. In fact, in the Delta yhm1 mutant, iron was found to accumulate in mitochondria. The accumulated iron showed decreased availability for haem synthesis, measured in isolated mitochondria using endogenously available metals and added porphyrins. The phenotypes of Delta yhm1 mutants indicate a role for this mitochondrial transporter in cellular iron homoeostasis.